Wordwall : Media Pembelajaran Inovatif Untuk Meningkatkan Minat Dan Hasil Belajar Siswa SMP Negeri 06 Bandung Pada Materi SPLDV - Muhtarom Nur Rasyid; Levina Lidya Maheswari; Hanifah El Faizah (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
Low student learning outcomes are influenced by several things, one of which is the learning media used. Innovation in the use of learning media is needed to improve student learning outcomes, especially in mathematics subjects. This makes researchers interested in conducting a wordwall games-based learning media experiment at SMP Negeri 06 Bandung. The purpose of this study was to determine the effectiveness of using wordwall learning media on improving student learning outcomes in mathematics subjects. The research method used is quantitative experiment with one group pretest-postest model with the population of class IX students of SMP Negeri 06 Bandung. The sampling technique uses cluster random sampling with the provision that students can access the browser as many as 18 students. Based on the N-Gain test, the average N-Gain value of 0.679056437 is included in the medium category and is quite effective. This shows that the use of Wordwall learning media has a significant impact on improving the mathematics learning outcomes of SMP Negeri 06 Bandung students.